急性の医学的状態の潜在的な発症を判定するための方法及び装置 (2024)
Disclosed is a method of managing risk, of a subject, of suffering an adverse condition relating to a physiological system of the subject. The method includes a. providing a wearable acoustic sensor, b. providing a data processor, and c. causing the processor to i. monitor the output from the sensor, ii. apply a predictive numerical model to generate a prediction, iii. compare the prediction with the sensor output, and iv. determine a response on the basis of the comparison.